University Teaching in Global Times: Perspectives of Italian University Faculty on Teaching International Graduate Students. (July 2022) - Coryell, Joellen E.; Cinque, Maria; Fedeli, Monica; Lapina Salazar, Angelina; Tino, Concetta
Recently, many Italian universities began offering graduate courses or entire programs in English to attract international students, assist domestic students with English language proficiency, and internationalize the learning experience for all. This research investigated Italian faculty's perspectives on their experiences of teaching international graduate students. The article begins with an overview of European university internationalization and then reviews the literature on faculty perspectives on teaching international students and instructional professional development for internationalization of teaching and learning. Findings include participant demographics and faculty perspectives on teaching international graduate students as compared with domestic students, their current and desired ways of learning how to teach international students, and their recommendations for faculty teaching in international programs/courses with English as the language of instruction. Implications for instructional professional development, communities of instructional practice, and further research are offered.